2009
DOI: 10.1111/j.1750-3841.2009.01101.x
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Content and Antioxidant Activity of Primitivo Wine: Comparison among Winemaking Technologies

Abstract: The aim of this study was to assess the influence of 9 winemaking technologies (traditional, delestage, saignée, delayed punching-down, addition of grape seed tannins, addition of ellagic-skin-seed tannins, heating of must-wine, cryo-maceration, and prolonged maceration) on the phenolic content and antioxidant activity of Primitivo musts and wines. Three methods for the determination of the antioxidant activity were compared: DPPH, beta-carotene bleaching assay, and ABTS. Oenological parameters and composition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
52
1
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 29 publications
9
52
1
3
Order By: Relevance
“…The lowest concentrations were obtained for the addition of tannins (52.25 mg L -1 for Feteasca Neagra and 51.14 mg L -1 for Negru Aromat). These results are in agreement with the data published by Baiano et al (2009), who considered that the small levels of anthocyanidins in wine obtained by the addition of tannins is a consequence of the formation of bonds between tannins and anthocyanidins.…”
Section: Influence Of Winemaking Technologysupporting
confidence: 95%
“…The lowest concentrations were obtained for the addition of tannins (52.25 mg L -1 for Feteasca Neagra and 51.14 mg L -1 for Negru Aromat). These results are in agreement with the data published by Baiano et al (2009), who considered that the small levels of anthocyanidins in wine obtained by the addition of tannins is a consequence of the formation of bonds between tannins and anthocyanidins.…”
Section: Influence Of Winemaking Technologysupporting
confidence: 95%
“…Red wines have a very complex phenolic composition that depends on the grape variety used, but also it is strongly affected by winemaking techniques and oenological practices (Baiano, Terracone, Gambacorta, & La Notte, 2009;Cantos, Espín, & Tomás-Barberán, 2002;Sun, Spranger, Roque-do-Vale, Leandro, & Belchior, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Different studies on thermovinification have found that the concentration of anthocyanins increases (Lowe et al, 1976;Sacchi et al, 2005;Baiano et al, 2009), while the concentration of the flavonoids remains low (Sacchi et al, 2005;Baiano et al, 2009). In one study, Wagener (1981) found that the wine made from systems (Imeca and Sernagiotto plants) in which they used a destemmer and final press was very dark in colour and astringent.…”
Section: Thermovinificationmentioning
confidence: 99%
“…Methods like cold soaking/maceration (McMahon et al, 1999, Gómez-Plaza et al, 2000, Álvarez et al, 2009Gil-Muñoz et al, 2009) could release more colour from grape skins, while post-fermentation maceration (Zimmer et al, 2002) could release more tannins, as the alcohol will help in releasing the tannins. Thermovinification (Lowe et al, 1976, Sacchi et al, 2005Baiano et al, 2009) and carbonic maceration (Gómez-Míguez & Heredia, 2004;Sacchi et al, 2005;Etaio et al, 2008) can also be used to extract anthocyanins and tannins from the skins. These methods will have variable success, as wines made from carbonic maceration will have a lighter colour but will be fruitier (Etaio et al, 2008).…”
Section: Introductionmentioning
confidence: 99%